2020
DOI: 10.1186/s43088-020-00057-9
|View full text |Cite
|
Sign up to set email alerts
|

Polylactic acid-based electrospun fiber and hyaluronic acid-valsartan hydrogel scaffold for chronic wound healing

Abstract: Background: In this study, the chronic wound healing ability of PLA-based electrospun nanofibers loaded with hyaluronic acid, valsartan, and ascorbic acid is explored. PLA-based scaffolds were fabricated by electrospinning, followed by loading the scaffolds with different concentrations of hyaluronic acid, valsartan, and ascorbic acid hydrogels. The produced formulations were characterized by scanning electron microscopy imaging (SEM), tensile strength testing, Fourier-transform infrared spectroscopy (FTIR), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 30 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…It is a widely used polymer in nanofibers fabrication, which is obtained by polymerization of lactide for diabetic wound healing purposes [ 71 ]. It is usually crosslinked with other polymers, such as gelatin, to enhance its cell adhesion properties, or it is combined with biomaterials such as silver nanoparticles for wound dressing purposes to curb microbial growth in infected wounds [ 30 ].…”
Section: Polymers Used In the Fabrication Of Nanofibrous Scaffoldsmentioning
confidence: 99%
“…It is a widely used polymer in nanofibers fabrication, which is obtained by polymerization of lactide for diabetic wound healing purposes [ 71 ]. It is usually crosslinked with other polymers, such as gelatin, to enhance its cell adhesion properties, or it is combined with biomaterials such as silver nanoparticles for wound dressing purposes to curb microbial growth in infected wounds [ 30 ].…”
Section: Polymers Used In the Fabrication Of Nanofibrous Scaffoldsmentioning
confidence: 99%
“…The results of reepithelization study revealed that the PLA-valsartan-based hydrogel scaffold-treated groups showed 1.43-folds increase in reepithelialization rate as compared to neomycin-based dressings. In addition, PLA-valsartan-based hydrogel scaffold-treated groups exhibited 2.5-folds increase in wound closure as compared to neomycin-based dressing-treated groups [ 168 ].…”
Section: Materials Used In Scaffold Fabricationmentioning
confidence: 99%
“…PLA-based electrospun fibers loaded with hyaluronic acid-valsartan hydrogels have been shown to be stable and possess proven diabetic wound healing property. This was as a result of the known biomimetic effect of the fibers and increased reepithelization facilitated by the hydrogels containing angiotensin inhibitors which is facilitated by the presence of hyaluronic acid as the ECM components [43].…”
Section: Elastin and Fibronectinmentioning
confidence: 99%